Analisis Perbandingan Protokol Transport Pada Video Streaming di Jaringan Lokal (LAN) Menggunakan Videolan Client - Riska Riska; Hendri Alamsyah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
The use of video streaming on computer networks uses the method of delivering multimedia content in the form of streaming that can be done with several transport protocols such as RTP, RTSP, and HTTP. The protocol has its own character and of course also has its own quality comparison. Therefore, this study will compare the quality of each of these protocols. The assessment criteria to be carried out in this study are the value of throughput, delay and jitter. Streaming video will be done with the VLC application and measuring the quality of services using the Wireshark application. From the results of the testing that the author did, the best video streaming quality on the local network is using HTTP protocol with a throughput value of 418.635 kbps, Delay 8.65 ms, and jitter 19,618 ms.